A modified technique for retention of orbital prosthesis - Sameera R Shaikh; Pravinkumar G Patil; Santosh Puri (Wolters Kluwer Medknow Publications, 2011)
An orbital defect (congenital or acquired) causes severe facial asymmetry and disfigurement, which results in psychological and social disturbances to the patient. It becomes a challenging task for a maxillofacial prosthodontist to fabricate a prosthesis that replicates the healthy side of the face. Success of the prosthesis depends primarily on satisfactory retention of the same. This clinical report illustrates rehabilitation of a patient with an orbital defect by fabricating a hollow orbital prosthesis, utilizing anatomical undercuts for retention using an acrylic resin template relined by a resilient denture liner.